2006
DOI: 10.1902/jop.2006.77.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Alkaline Phosphatase Levels in Postmenopausal Women: Effects of Phase I Periodontal Treatment

Abstract: These data suggest that the presence of ALP in GCF is not simply a reflection of the local inflammation state and that a patient's estrogen status may possibly influence local ALP levels in GCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 36 publications
1
30
0
2
Order By: Relevance
“…The GCF serum ratio for clinically healthy periodontal tissues ranged from 6:1 to 12:1, which implies that the enzyme is locally produced within the periodontium. [28] Thus, gingival crevicular fluid ALP levels from periodontal pockets can be taken as indicative for active periodontal tissue destruction. Chapple et al .…”
Section: Discussionmentioning
confidence: 99%
“…The GCF serum ratio for clinically healthy periodontal tissues ranged from 6:1 to 12:1, which implies that the enzyme is locally produced within the periodontium. [28] Thus, gingival crevicular fluid ALP levels from periodontal pockets can be taken as indicative for active periodontal tissue destruction. Chapple et al .…”
Section: Discussionmentioning
confidence: 99%
“…La fal tiene la particularidad de estar involucrada con la inflamación y con la reparación/regeneración, utilizándose como un marcador inflamatorio del periodonto, así como del metabolismo óseo, mediante su dosaje en fgc y suero [10][11][12][13].…”
Section: Discussionunclassified
“…16 Daltaban et al reported higher GCF ALP levels in post-menopausal women with periodontitis than in the clinically healthy control group. 17 A recent study, demonstrated low levels of GCF ALP in non-destructive and slightly destructive periodontitis sites, whereas significantly high levels of ALP were observed in moderately and severely destructive sites. 18 In the present study, there was no significant difference between the study groups including between CP and H suggesting that the destruction was moderate in the sampling sites of the CP group or might be even a little destruction or subclinical inflammation in H group.…”
mentioning
confidence: 93%
“…26,27 It is well known that the homeostasis in bone turnover is disturbed during the progression of periodontal disease and leads to irreversible bone resorption where the immune cells and cytokines released play an important role. 17 The presence of measurable amounts of GCF ALP, OC, OPN, OPG and PTH in the CP, G and H groups might be due to the bone homeostasis process independently ageing. Our study results, for the first time, demonstrated the presence of bone turnover markers in the GCF of elderly individuals with different periodontal disease.…”
mentioning
confidence: 96%
See 1 more Smart Citation